Personality pathology grows up: adolescence as a sensitive period. (June 2018) - Sharp, Carla; Wall, Kiana
Highlights: Personality pathology onsets in adolescence. Personality pathology is moderately stable in adolescence. Personality pathology is preceded by internalizing and externalizing disorders. Personality pathology remains comorbid with internalizing and externalizing pathology throughout development. Personality pathology emerges as maladaptive self-other relatedness from normative adolescent identity development. Abstract : There is mounting evidence that personality pathology, in particular, borderline pathology is a valid and reliable construct in adolescence, with prevalence, phenomenology, stability and risk factors similar to that of adult borderline personality disorder. Scientific evidence also delineates a marked separation of course and outcome of adolescent borderline personality disorder from other disorders and supports the efficacy of disorder-specific treatment. The current article addresses recent findings in these areas which point to adolescence as a sensitive period for the development for personality pathology. A conceptual model of psychopathology is presented wherein personality pathology is described as a qualitatively different level of psychopathology in the form of maladaptive self-other relatedness that is developmentally tied to identity formation in adolescence.